Dynamic Simulations of the Allam Cycle Power Plant Integrated with an Air Separation Unit - Dan Fernandes; Song Wang; Qiang Xu; Daniel Chen (International Journal of Chemical Engineering)
The unprecedented rise in carbon dioxide levels due to anthropogenic activities, if left unchecked, can lead to increased global warming. Electricity and heat generation account for around 25% of this greenhouse gas emission. The Allam cycle, a new oxy-fuel power cycle that emits virtually no CO2 and NOx, is inherently integrated with an air separation plant. In this study, Aspen Plus Dynamics was used to model the integrated Allam power plant/air separation unit (ASU) with a high degree of heat and work integration. The steady-state model developed agrees with the model developed by Net Power. Regulatory and advanced PID controllers were implemented for major equipment to meet operation objectives. Controller set point change, power ramp down, and natural gas composition change were studied, and key plant performance indicators were monitored and analyzed. This study shows that the Allam cycle power plant integrated with an ASU is controllable with the proposed control strategy under a tightly integrated configuration.